SAT-460 Myxedema Coma Mimicking Cardiogenic Shock Treated with Levothyroxine - Chaker, Bayan (J Endocr Soc, 2020)
Myxedema coma is a medical emergency with a mortality rate of 30–50%. It is a commonly missed diagnosis and can lead to multiple cardiovascular complications which are reversible with levothyroxine treatment. IV levothyroxine should be initiated based on clinical suspicion without waiting for laboratory results. We report a case of a 71-year-old female with a history of CABG 10 years ago, who presented to the emergency department with a syncopal episode. The patient denied aura, vomiting, jerky movements, rolling eye movements, bowel/bladder incontinence, and palpitations. She reported having exertional chest pain for a couple of months. Her home medications included metoprolol succinate 50 mg daily, hydralazine 50 mg twice daily, Imdur 30 mg daily, and levothyroxine 300 mcg daily which the patient reported taking rarely. On admission, the temperature was 36°C, HR 43, BP 75/49 which dropped to 60/40, RR 9, and SpO2 of 93% on 2LPM. Physical exam showed euvolemia with brisk reflexes and delayed relaxation. Blood work revealed Na of 133 mM/L (L), Cr 6.4 mg/dL (H) from a baseline of 2.4 mg/dL, and a troponin of 0.26 ng/mL (H). EKG showed first degree AV block with new T-wave flattening not seen on previous EKGs. A fluid challenge for hypotension elicited no response and the patient was started on a dopamine drip for cardiogenic shock, a heparin drip for ACS, and was transferred to the CCU. BP improved to 140s/70s with a HR remained in the 50s. On the 2nd day of admission, blood work revealed a TSH of >150 (H), free T4 of 0.6, total T3 of 34 (L) and a random cortisol of 15.5 microgram/dL. On the 3rd day of admission, the patient was given 200 mcg of IV levothyroxine. At that time, the patient was on a dopamine drip with a BP of 144/94 with a HR of 64. Twelve hours later, the patient’s BP went up to 197/105 with a heart rate of 65 prompting discontinuation of the dopamine drip and administration of hydralazine and amlodipine. On the morning of the fourth day of admission, BP went up to 236/116 with a HR of 75 and the patient was started on a nicardipine drip. Blood work 3 days after starting levothyroxine revealed a TSH of >150, free T4 of 0.9, and a total T3 of 70. The patient was discharged on levothyroxine 150 mcg daily, amlodipine 10 mg, hydralazine 50 mg q6hrs, and Imdur 30 mg daily. The patient’s myxedema score was 75 on admission. However, thyroid function tests were not checked with initial labs despite the presence of avert clinical features. As a result, the patient was started on a dopamine drip which could have been avoided. This underlines the importance of early recognition and management of myxedema coma. Having a low total T3 with a low normal FT4 could be explained by recent intake of high dose levothyroxine at home after a significant period of non-compliance. Fortunately, levothyroxine administration to this patient has reversed cardiovascular abnormalities including bradycardia and hypotension within hours when it was given promptly.